ANALISIS KESALAHAN BERBAHASA DALAM INTERAKSI JUAL BELI DI PASAR MMTC MEDAN - Ezra Parida Sitinjak; Intan Dwi Angel Panjaitan; Nurul Afni; Syahriani Nasution; Tia Septy Monica Sinaga (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze language use in buying and selling interactions at MMTC Market Medan. This research used a descriptive qualitative method with observation, interviews, and note-taking techniques. The results showed that Indonesian is the dominant language used by traders and buyers because it is easier to understand. Regional languages such as Nias and Batak Toba are still used in certain situations according to the background of the speakers. The findings indicate that significant language errors were rarely found. Instead, language variation and code-mixing were used to support effective communication. Factors influencing language use include ethnic background, social environment, and daily language habits.